تقييم دور جامعة تشرين في بناء مجتمع المعرفة من وجهة نظر عينة من أعضاء الهيئة التعليمية فيها - الصطوف محمد الحسين; صبيح محمد ياسين; غصن رولا نسيم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن العملية التنموية اليوم أضحت معتمدة في مجالاتها كافة على المعرفة وأصبح الاستثمار في مجال المعلومات والمعارف يمثل واحداً من أهم أوجه الاستثمار الإنساني والاجتماعي، وبذلك أصبحت المعرفة اليوم تشكل معياراً للرقي الإنساني، وانطلاقاً من أهمية هذه المعرفة ومن أن المؤسسات التعليمية عامة ومؤسسات التعليم العالي خاصة تلعب الدور الأكبر في بناء مجتمع المعرفة فقد ارتأينا أن نقوم من خلال هذا البحث بإلقاء الضوء على واقع الدور الذي تؤديه جامعة تشرين في هذا المجال من وجهة نظر عينة من أعضاء الهيئة التعليمية فيها. وقد أظهرت نتائج الدراسة أن الدور العام لجامعة تشرين في بناء مجتمع المعرفة وفق تقديرات أعضاء الهيئة التعليمية فيها كان متوسطاً. ودلت النتائج أيضاً على عدم وجود فروق دالة إحصائياً بين إجابات الجنسين في كل من المجالات الثلاثة (توليد المعرفة – تنمية مجتمع المعرفة – إعداد الفرد)، بينما أظهرت النتائج من جهة أخرى وجود فروق جوهرية بسبب الاختصاصات في هذه التقديرات في مجالي توليد المعرفة وإعداد الفرد وذلك لصالح الأقسام النظرية، وعدم وجود فروق دالة إحصائياً في تقديرات عينة الدراسة في مجال تنمية مجتمع المعرفة تبعاً لمتغير الاختصاص. أوصت الدراسة بضرورة أن تعطي جامعة تشرين اهتماما أكبر بالجوانب المتعلقة ببناء مجتمع المعرفة، وذلك من خلال التعاون مع مواقع الإنتاج والخدمات في المجتمع، تطوير الموقع الإلكتروني للجامعة، إجراء المزيد من الدراسات المتعلقة بالموضوع المدروس، تشجيع الابتكار. Today, development is based in all dimensions on knowledge, and the investment in this dimension is one of the most important obverses of investment. So, the knowledge has become the criterion of the progress .Starting from the importance of this knowledge and the role of the didactic institutions in general and the role of higher education institutions in particular in structuring the society of knowledge, this leads us in this study to investigate the role of the Tishreen University in structuring the knowledge society from the perspective of their teaching staff members. After data collection and analysis, it was revealed that the Tishreen University, according to staff members, has played a medial role in structuring knowledge society. Additionally, the results showed that there were no significant differences in the role of Tishreen University in this dimension due to gender. However, the results showed significant differences in the role of Tishreen University in preparing individual and generating knowledge due to specialization variable in favor of literary specialization, but there were no significant differences in the role of Tishreen university in developing knowledge society due to the specialization. The study recommends that Tishreen University should pay more attention to topic of structuring the knowledge society by co-operating with establishment of producing and services in society, developing its web site, making more studies about this subject and encouraging innovation.